Levothyroxine treatment of euthyroid children with autoimmune Hashimoto thyroiditis: results of a multicenter, randomized, controlled trial - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Karges, Beate Maria; Kneppo, Carolin; Schmidt, Heinrich; Voss, Egbert; Wabitsch, Martin; Dötsch, Jörg (Hormone research in paediatrics, 2015)
Background: Levothyroxine (L-T4) treatment of euthyroid children with Hashimoto thyroiditis (HT) is a controversial issue. Patients and Methods: We conducted a prospective, randomized, controlled clinical trial. Out of 79 identified euthyroid patients, 59 started the study; 25 patients (21 female, 4 male; age: 11.8 ± 2.3 years) received L-T4 at a mean dose of 1.6 µg/kg (SD, 0.8) daily, and 34 (27 female, 7 male; age: 12.6 ± 1.2 years) were not treated. Patients developing subclinical hypothyroidism during follow-up (n = 13) were treated with L-T4 and removed from the observation group. As the main outcome measures, thyroid gland volume (determined by ultrasound) as well as serum levels of TSH, free T4, and antibodies against thyroid peroxidase and thyroglobulin were assessed every 6 months for 36 months. Results: At the start, the mean thyroid volume (standard deviation score, SDS) was 2.5 in the treatment group and 1.6 in the observation group. There was a constant decline in mean thyroid volume (SDS) from 2.13 (month 12) to 1.12 (month 30) in the treated group, with a delta thyroid volume of -1.01 SDS. In the observation group, the mean delta thyroid volume increased to +0.27 SDS. The change of the delta thyroid volume was statistically significantly different between both groups during the 12- and 30-month time points (p < 0.05). L-T4 had no effect on thyroid function and serum thyroid antibodies. Conclusions: L-T4 treatment can decrease the thyroid volume in euthyroid children with HT, but the effect is limited to a definite time period.
Gesehen am 23.06.2020